Hepatic peroxisome proliferator-activated receptor γ and α-mRNA expression in HCV-infected adults is decreased by HIV co-infection and is also affected by ethnicity (Clinics, 2015)
OBJECTIVE: To determine peroxisome proliferator activated receptor α and γ mRNA expression in liver tissue of hepatitis C virus-infected patients with and without human immunodeficiency virus and its possible contribution to an acceleration of liver disease progression. METHODS: We measured peroxisome proliferator-activated receptor α and γ mRNA expression by real-time polymerase chain reaction in liver tissues from 40 subjects infected only with hepatitis C virus, 36 subjects co-infected with hepatitis C virus and human immunodeficiency virus and 11 normal adults. RESULTS: Hepatic mRNA expression of both peroxisome proliferator-activated receptors was significantly lower in hepatitis C virus-infected subjects with and without human immunodeficiency virus co-infection compared to the controls. Non-black race was also identified as a predictor of lower peroxisome receptor α and γ mRNA expression. Compared to subjects infected only with hepatitis C virus, liver peroxisome receptor γ mRNA expression was significantly lower in hepatitis C virus/human immunodeficiency virus-co-infected subjects (0.0092 in hepatitis C virus/human immunodeficiency virus-co-infection vs. 0.0120 in hepatitis C virus-only; p=0.004). Hepatic peroxisome receptor α mRNA expression in the hepatitis C virus-infected patients was lower in the presence of human immunodeficiency virus co-infection in non-black subjects (0.0769 vs. 0.1061; p=0.02), whereas the levels did not vary based on human immunodeficiency virus status among black subjects. CONCLUSION: mRNA expression of both peroxisome proliferator-activated receptors is impaired in hepatitis C virus-infected liver and further reduced by human immunodeficiency virus co-infection, although the suppressive effects of the viruses are substantially mitigated in black patients.